2001
DOI: 10.1038/85454
|View full text |Cite
|
Sign up to set email alerts
|

In vivo gene therapy of metachromatic leukodystrophy by lentiviral vectors: correction of neuropathology and protection against learning impairments in affected mice

Abstract: Metachromatic leukodystrophy (MLD) is a lipidosis caused by deficiency of arylsulfatase A (ARSA). Although the genetics of MLD are known, its pathophysiology is not understood. The disease leads to progressive demyelination and early death and no effective treatment is available. We used lentiviral vectors to deliver a functional ARSA gene (human ARSA) into the brain of adult mice with germ-line inactivation of the mouse gene encoding ARSA, As2. We report sustained expression of active enzyme throughout a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
105
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 198 publications
(109 citation statements)
references
References 41 publications
3
105
0
1
Order By: Relevance
“…In addition, we observed tissue damage after expression of Cre for several weeks in the brain. With use of lentiviral vectors that carry other transgenes, we and others have observed long-term expression of the transgenes without obvious indications of tissue damage (18,24,35). Cre-induced cytotoxicity might be an explanation for the reduced number of Cre-expressing, ␤-gal ϩ cells that we observed in vitro and after prolonged (3-5 weeks) Cre expression in the brain.…”
Section: Discussionmentioning
confidence: 61%
“…In addition, we observed tissue damage after expression of Cre for several weeks in the brain. With use of lentiviral vectors that carry other transgenes, we and others have observed long-term expression of the transgenes without obvious indications of tissue damage (18,24,35). Cre-induced cytotoxicity might be an explanation for the reduced number of Cre-expressing, ␤-gal ϩ cells that we observed in vitro and after prolonged (3-5 weeks) Cre expression in the brain.…”
Section: Discussionmentioning
confidence: 61%
“…Many invasive strategies have been used or proposed for circumventing the blood-brain barrier, including intraparenchymal injections of therapeutic proteins, intraparenchymal gene therapy, chemical or physical agents to open the blood-brain barrier (such as mannitol), and hematopoietic stem cell transplantation [1][2][3][4][5][6][7][8][9]. Treatment via the cerebrospinal fluid has not been successful in the past due to the inability of the proteins to traverse the ependymal layer and diffuse through brain tissue, even though this route would be clinically easier for application to patients.…”
Section: Introductionmentioning
confidence: 99%
“…2 The direct injection of viral vectors into the brain parenchyma allows only a restricted diffusion-few centimeters away from the injection site-of viral particles and large molecules (except for proteins actively transported by neurons). 3,4 Systemic as well as intraparenchymal delivery of viral vectors usually induces humoral and cell-mediated immune responses against the vectors and/or transgene products, leading to inflammation, short-term persistence of gene expression and elimination of transduced cells. [5][6][7] We, and others, have previously shown that injection of viral vectors into the cisterna magna, or trough lumbar puncture, might represent an efficient CNS delivery system in both small (mice) and large (non-human primates) animals.…”
Section: Introductionmentioning
confidence: 99%